2017
DOI: 10.1101/gad.284661.116
|View full text |Cite
|
Sign up to set email alerts
|

Neat1 is a p53-inducible lincRNA essential for transformation suppression

Abstract: The p53 gene is mutated in over half of all cancers, reflecting its critical role as a tumor suppressor. Although p53 is a transcriptional activator that induces myriad target genes, those p53-inducible genes most critical for tumor suppression remain elusive. Here, we leveraged p53 ChIP-seq (chromatin immunoprecipitation [ChIP] combined with high-throughput sequencing) and RNA-seq (RNA sequencing) data sets to identify new p53 target genes, focusing on the noncoding genome. We identify Neat1, a noncoding RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
191
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(196 citation statements)
references
References 94 publications
4
191
0
1
Order By: Relevance
“…We and others have shown that p53 also directly upregulates several microRNAs including miR-34a and miR-3189 , which, in turn, suppress gene expression downstream of p53 (Chang et al, 2007, Lal et al, 2011, Hermeking, 2012, Jones et al, 2015, Raver-Shapira et al, 2007). More recently, we and others have demonstrated specific functions of a number of p53-regulated lncRNAs, including lincRNA-p21 , PANDA , DINO , PINT , PR-lncRNA-1 , LED , linc-475, NEAT1 and PINCR (Huarte et al, 2010, Dimitrova et al, 2014, Hung et al, 2011, Marin-Bejar et al, 2013, Sanchez et al, 2014, Leveille et al, 2015, Melo et al, 2016, Schmitt et al, 2016, Adriaens et al, 2016, Mello et al, 2017, Chaudhary et al, 2017). Although these studies illustrate the importance of lncRNAs in the p53 network as well as the functional heterogeneity of p53-regulated lncRNAs, the function of the vast majority of p53-regulated lncRNAs remains to be elucidated.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…We and others have shown that p53 also directly upregulates several microRNAs including miR-34a and miR-3189 , which, in turn, suppress gene expression downstream of p53 (Chang et al, 2007, Lal et al, 2011, Hermeking, 2012, Jones et al, 2015, Raver-Shapira et al, 2007). More recently, we and others have demonstrated specific functions of a number of p53-regulated lncRNAs, including lincRNA-p21 , PANDA , DINO , PINT , PR-lncRNA-1 , LED , linc-475, NEAT1 and PINCR (Huarte et al, 2010, Dimitrova et al, 2014, Hung et al, 2011, Marin-Bejar et al, 2013, Sanchez et al, 2014, Leveille et al, 2015, Melo et al, 2016, Schmitt et al, 2016, Adriaens et al, 2016, Mello et al, 2017, Chaudhary et al, 2017). Although these studies illustrate the importance of lncRNAs in the p53 network as well as the functional heterogeneity of p53-regulated lncRNAs, the function of the vast majority of p53-regulated lncRNAs remains to be elucidated.…”
Section: Introductionmentioning
confidence: 88%
“…Therefore, it is difficult to predict whether a given lncRNA is functional or reflects transcriptional noise. LncRNAs are regulated by the same transcription factors that regulate protein-coding genes, and increasing evidence suggests that the master-regulatory transcription factor p53, controls the expression of subset of lncRNAs (Grossi et al, 2016, Chaudhary and Lal, 2016, Adriaens et al, 2016, Mello et al, 2017, Chaudhary et al, 2017). Coordinated regulation of even low-abundance lncRNAs indicates that many lncRNAs have undiscovered, yet critical functions in cell biology and disease.…”
Section: Introductionmentioning
confidence: 99%
“…52 In pancreatic cancer, NEAT1 was a p53-inducible lncRNA essential to suppress transformation. 53 The paradoxical outcome mirrors labyrinthine controlling networks of NEAT1 and provokes our greater interest in NEAT1.…”
Section: Discussionmentioning
confidence: 99%
“…However, Neat1 and paraspeckles are only present in a subpopulation of cells in certain mouse tissues and their loss does not have overt phenotypic effects on development or overall survival in mice, indicating that these nuclear bodies are not essential and only relevant under certain physiologic or pathophysiologic conditions. For example, later studies revealed critical functions for Neat1 in female fertility and lactation, as well as a role in the p53 tumor suppressor pathway and tumorigenesis . However, the mechanism of how Neat1 and paraspeckles regulate these functions in vivo is still unclear.…”
Section: Regulation and Organization Of Nuclear Structures By Lncrnasmentioning
confidence: 99%
“…For example, later studies revealed critical functions for Neat1 in female fertility and lactation, 75,76 as well as a role in the p53 tumor suppressor pathway and tumorigenesis. [77][78][79] However, the mechanism of how Neat1 and paraspeckles regulate these functions in vivo is still unclear.…”
Section: Rna Interactions In Mammalian Cells Indeed Revealed That Malat1mentioning
confidence: 99%